Treatment of early stage vaginal cancer with EBRT and MRI-based intracavitary brachytherapy: A retrospective case review - Shari Damast, MD; Vinita Takiar, MD, PhD; Shirley McCarthy, MD, PhD; Susan A. Higgins, MD, MS (Elsevier, 2016)
This case series describes the use of pelvic radiotherapy (RT) and MRI-based intracavitary brachytherapy (ICBT) for patients with small volume, early-stage, primary vaginal cancer. A customized pelvic MRI protocol with a vaginal cylinder in place (MRVC) was used to measure disease extent and tumor thickness (defined as distance from lateral/apical margin of tumor to cylinder surface) at time of diagnosis. Non-bulky tumors with initial (pre-RT) thickness ≤ 2 cm from the cylinder surface received pelvic RT followed by ICBT. Ten patients with FIGO stage I-II primary vaginal cancer treated with pelvic RT +/− cisplatin and ICBT at our institution between 1998 and 2008 were included. Initial tumor thickness measured on MRVC ranged from 0 to 2 cm. Initial tumor volume ranged from 0 to 9.8 cm3. Mean pelvic RT dose was 45 Gy. At the time of ICBT, 60% of patients had a complete response (cR) and 40% had a partial response (pR). No patients with a cR had a recurrence whereas one patient with a pR had a local recurrence following ICBT. For the entire cohort, the median follow-up time was 59.9 months (range: 15-153). The estimated 5-year overall survival, disease-specific survival, and local failure-free survival were 67%, 80%, and 90%, respectively. Among survivors, there were no late grade 3-4 toxicities. In this series of patients with small primary early-stage vaginal tumors, long term clinical outcomes were acceptable following RT and MRI-based ICBT, especially among those with a cR at time of brachytherapy.